A Community Based Study on Care Practice and Attitudes on male Circumcision in Muslim Community of Arghakanchi District, Nepal - Paudel, Mohan; Mehata, Suresh (Journal of Manmohan Memorial Institute of Health Sciences, 2014)
Male circumcision is an obligatory religious or puberty rite among Muslims, Jews, Africans, and some other peoples. When, where, how, and by whom the operation is performed vary from group to group. The study was conducted in Pali VDC of Arghakhanchi district. Pali VDC is situated about 22 kilometers in the east from Sandhikharka, the headquarter of the district. It covers about 125 hectors land and is divided into 9 wards. It has 5500 populations in an average. There is one secondary school, one lower secondary school and two primary schools. The Muslim population resides entirely in ward no-1, 2, 3 & 4 of the VDC. The practices regarding circumcision and health seeking behaviour seems not very satisfactory as the practice so far has not been conducive to health of the children. This has been carried out nearly 100% by Hazam who is not health worker and hospitalization of circumcision is almost absent. Only small proportion of cases of circumcision (22%) during post circumcision period have sought for health institutions. However, looking at the use of modern medicines (injections/ tablets/capsules) during circumcision by about 23% shows the hope for improvement. People?s attitudes regarding circumcision seems far better than the practices that are currently prevalent in the community. The higher share of people in favor of hospitalization (91%) and the opinions of majority (62%) as health workers the appropriate decision maker makes the sign of possible intervention program to be successful. DOI: http://dx.doi.org/10.3126/jmmihs.v1i1.9898 Journal of Manmohan Memorial Institute of Health Sciences Vol.1(1) 2011; 30-35